ISLAMIC LAW REVIEW OF THE CONSIGNMENT AGREEMENT FOR THE SALE OF FREE-RANGE CHICKEN EGGS: STUDY OF IJARÂH 'ALA AL-'AMÂL CONTRACT - Aldi Hafsani; Mkhwanazi, Lindani (JURISTA: Jurnal Hukum dan Keadilan, 2024)
The aim of this research is to understand the business carried out, investigate the marketing methods applied and examine the agreement to sell free-range chicken eggs through a consignment system based on a review of the ijarah 'ala al-'amal contract in the Kuta Baro District area. Researchers used observation and interview methods to collect data. This research uses a descriptive approach to process data to draw conclusions about the consignment-based sales system within the framework of the ijarah 'ala al-'amal contract in the Kuta Baro District area. The research results show that free-range chicken egg business owners have reached informal agreements with several coffee shops and cafes to place their products. Sales of free-range chicken eggs are regulated through a consignment system with profit sharing usually calculated based on a percentage of total sales, namely 80% for egg owners and 20% for coffee shop or cafe managers. Ijārah ‘Ala Al-‘Amāl is an agreement that regulates the use of someone's services for certain tasks with commercial purposes that generate profits, such as delivering customer orders to the desired location. Types of work that combine these aspects are generally found among entrepreneurs cultivating free-range chicken eggs. Village chicken egg entrepreneurs market their products by handing over their eggs to sell to various places such as shops, kiosks and coffee shops. In this case they use a consignment system where the eggs are entrusted to the shop which then sells them to buyers.